PENGARUH PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PEMBELAJARAN EKONOMI DALAM MENINGKATKAN MINAT BELAJAR SISWA SMA RAKYAT SEI GLUGUR - Pasaribu, Ida Aryani; Sulaiman, Sulaiman; Rijal, Anggriani, (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
The role of technology is vital, especially for people in developing countries. The government and society pay maximum attention to technology development today because they realize the role and function of technology are very important for life. Education is the primary need of every human being that can improve human dignity. Moreover, in the 21st century, education faces severe challenges, namely the challenge of globalization, which requires every human being to master knowledge and technology, for those who do not have an education will automatically be excluded from global competition. One of the steps that can be taken to advance the education sector is by innovating in the delivery of learning materials. This study aims to conduct the Development of Economic Interactive Learning Media to Increase Learning Interest of Students of Sei Glugur People's High School. This research method uses a Research and development (R&D) design that adopts development. The subjects in this study were students of Sei Glugur People's High School. The data collection instrument used was the results questionnaire. The development of this learning media resulted in a learning media where the media made a difference in the learning process of Canva-based interactive media after several trials. Conclusion. The preparation of Canva-based interactive media development can increase student interest in learning.